2007
DOI: 10.1007/s00421-006-0388-1
|View full text |Cite
|
Sign up to set email alerts
|

Intense hypoxic cycle exercise does not alter lung density in competitive male cyclists

Abstract: We tested the hypothesis that intense short duration hypoxic exercise would result in an increase in extravascular lung water (EVLW), as evidenced by an increase in lung density. Using computed tomography (CT), baseline lung density was obtained in eight highly trained male cyclists (mean +/- SD: age = 28 +/- 8 years; height = 180 +/- 9 cm; mass = 71.6 +/- 8.2 kg; VO2max= 65.0 +/- 5.2 ml kg min(-1)). Subjects then completed an intense hypoxic exercise challenge on a cycle ergometer and metabolic data, HR and %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
(72 reference statements)
3
18
0
Order By: Relevance
“…Interestingly, in the present study, alveolar–capillary membrane conductance, when considered alone or when corrected for differences in V c , returned to baseline values during recovery under all three exercise conditions. These findings are in agreement with previous studies by us and others which have recently demonstrated that normobaric hypoxic exercise may not be an adequate stimulus to increase lung water in normally-trained healthy humans (Gallagher et al 1988; Guenette et al 2007; Hanel et al 1994; Hodges et al 2007; MacNutt et al 2007; Snyder et al 2006). Therefore, as with previous studies, the present study provides no evidence that short-duration hypoxic exercise results in lung fluid accumulation in healthy but untrained subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in the present study, alveolar–capillary membrane conductance, when considered alone or when corrected for differences in V c , returned to baseline values during recovery under all three exercise conditions. These findings are in agreement with previous studies by us and others which have recently demonstrated that normobaric hypoxic exercise may not be an adequate stimulus to increase lung water in normally-trained healthy humans (Gallagher et al 1988; Guenette et al 2007; Hanel et al 1994; Hodges et al 2007; MacNutt et al 2007; Snyder et al 2006). Therefore, as with previous studies, the present study provides no evidence that short-duration hypoxic exercise results in lung fluid accumulation in healthy but untrained subjects.…”
Section: Discussionsupporting
confidence: 93%
“…The change in PV from SL to HYP was similar in both HH and NH, and the change in PV during exercise was also similar in both environments. Previous research demonstrated compelling radiographic evidence of pulmonary edema in athletes exercising in HH [40], while other studies found no lung water accumulation in humans exercising in NH [41,42]. Differences in fluid circulation and the trans alveolar-capillary membrane flux [43] may induce greater pulmonary vasoconstriction in HH and decrease O 2 diffusion via a decreased pressure gradient [13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one of the mechanisms by which hypoxia is thought to result in an increase in lung water is through an increase in pulmonary capillary pressures. Three relatively recent studies have demonstrated that exercise during hypoxia (even in trained individuals) does not result in an increase in lung water, although they likely had dramatic increases in pulmonary pressures given high cardiac outputs coupled with hypoxic pulmonary vasoconstriction (Guenette et al, 2007; Hodges et al, 2007; MacNutt et al, 2007). Of importance, three of our subjects (18%) demonstrated radiographic evidence for an increase in lung water with short-term hypoxic exposure which is in agreement with some previous estimates of the percentage of the population that is susceptible to high-altitude pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%